Penelitian mutu jas hujan dari PVC - Herminiwati, Herminiwati (Majalah Kulit, Karet, dan Plastik, 1988)
30 (thirty) samples of rainwear from PVC sheeting of 13 trade mark with various colour and style were tested for the purpose of this research. The quality of the rainwear is determined by the decisive factors of quality that ensure the materialâs strength and satisfactory wear as described in British is Standard and ASTM. The test results of the rainwear from PVC sheeting are compilled as follow : sheet thickness 0.1479 â 0.31663, transverse tear strength 7.82 â 22,42 kg/cm2, longitudinal tear strength 2.82 â 13.69 kg/cm2, strength of button attachment/stitch Â seam strengthÂ  1.19 â 4.66 kg, color fatness to daylight 111.56 â 155.10 hour at grade 4 grey scale and dimensional stability 1.66 â 6.12 %. The test result shows that the rainwear complies the requirements of blocking test as well as water penetration test.